PHYSICAL ACTIVITY OF STUDENTS AT A PEDAGOGICAL UNIVERSITY: ANALYSIS OF THE CURRENT STATE AND DETERMINANT FACTORS (Sport Science Research, 2026)
The article presents a comprehensive analysis of the level of physical activity among students at Pavlodar Pedagogical University named after A. Margulan, based on statistical processing of online survey results from 93 respondents in their 1st and 2nd years of study (all cases valid). The aim of the study was to identify the current state of motor activity, key determinants and barriers, as well as to develop recommendations for optimizing physical education and health promotion work at the university. The hypothesis regarding the non-compliance of activity levels with WHO recommendations was confirmed: 58% of students engage in physical activity only episodically (1-2 times per week as part of the curriculum), 14 minutes of moderate or 75 minutes of vigorous activity per week). The primary barriers include lack of time (58 %), high academic workload (43 %), and insufficient motivation (37 %), exacerbated by excessive screen time and daily routine constraints. Key motivators encompass improvement of health and appearance (55 respondents) and credit recognition for participation in sports sections (16 respondents). Factor analysis using the principal component method identified four latent factors: physical engagement and self-perceived fitness, motivational-institutional, health-limiting, and sedentary-dietary. Comparative analysis with data from other Kazakhstani universities (15-30 % additional activity) and global trends (50-75 % inactivity among students in Central Asia and Eastern Europe; 60-80 % in highly digitized countries) confirms that the situation in pedagogical universities reflects a typical regional and international pattern of hypodynamia. Recommendations include diversification of activity formats, implementation of a credit system for section attendance, infrastructure modernization, and programs to reduce sedentary behaviour. The study highlights the strategic role of pedagogical universities in shaping a culture of healthy lifestyles among future teachers, offering practical implications for university policy while acknowledging limitations related to self-reported data.
Keywords: physical activity; students; pedagogical university; factor analysis; physical inactivity; motivation; sports infrastructure